2015
DOI: 10.3892/ol.2015.4015
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric natural killer/T-cell lymphoma with diffuse CD30 expression and without CD56 expression: A case report

Abstract: The majority of natural killer (NK)/T-cell lymphomas occur in the nasal cavity and rarely involve the stomach. They possess a specific immunophenotype, with the expression of cluster of differentiation (CD)56, CD2 and CD3ε, but without CD3 expression. Few cases of NK/T-cell lymphoma have partial CD30 expression. The present study reveals a unique case of a 41-year-old female patient with gastric NK/T-cell lymphoma that did not express CD56 and diffusely expressed CD30. Immunohistochemical staining demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…To the best of the author's knowledge, only two cases of upper gastrointestinal CD56-negative ENKTCL-NT have been reported thus far. 14,15 Kim et al 14 reported a case of recurrence in the small intestine, particularly the duodenum, which was not a primary lesion like our case. Thus far, only Zhang et al 15 reported a primary gastric presentation, but they were not concerned with the clonal TCR gene and tumor cell lineage, unlike the present report.…”
Section: 6mentioning
confidence: 48%
See 1 more Smart Citation
“…To the best of the author's knowledge, only two cases of upper gastrointestinal CD56-negative ENKTCL-NT have been reported thus far. 14,15 Kim et al 14 reported a case of recurrence in the small intestine, particularly the duodenum, which was not a primary lesion like our case. Thus far, only Zhang et al 15 reported a primary gastric presentation, but they were not concerned with the clonal TCR gene and tumor cell lineage, unlike the present report.…”
Section: 6mentioning
confidence: 48%
“…14,15 Kim et al 14 reported a case of recurrence in the small intestine, particularly the duodenum, which was not a primary lesion like our case. Thus far, only Zhang et al 15 reported a primary gastric presentation, but they were not concerned with the clonal TCR gene and tumor cell lineage, unlike the present report. Moreover, considering available information regarding the typical immunophenotype of the tumor (i.e., CD56+) [4][5][6] and the reported rates of more than 70%, 4 the CD56−T-cell lineage in the present case is theoretically unique.…”
Section: 6mentioning
confidence: 48%
“…Indeed, it has been reported that ENKTCL may show CD30-positive expression and CD56-negative expression. 27 The findings of the absence of ALK expression and presence of EBER expression do not favor a diagnosis of ALCL. Therefore, in our case, based on the histopathologic features and the expression of CD2, CD3ε, granzyme B, TIA-1 and EBER, a diagnosis of ENKTCL with CD20 expression was favored.…”
Section: Pathological Findings and Resultsmentioning
confidence: 96%
“…In addition, the tumor cells possessed the CD30 positive and CD56 negative phenotype in a younger patient, consequently leading to an initial diagnosis of anaplastic large cell lymphoma (ALCL). Indeed, it has been reported that ENKTCL may show CD30‐positive expression and CD56‐negative expression . The findings of the absence of ALK expression and presence of EBER expression do not favor a diagnosis of ALCL.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of ENKTCL is highest in Asian and Latin American countries. Primary GI-NKTCL is extremely rare ( 1 3 ), with a limited number of reported cases and very few studies specifically focused on this subtype of NKTCL ( 34 37 ). Due to the rarity of the disease, the clinical, genomic and immune characteristics have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%